2008
DOI: 10.1089/adt.2008.134
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Olefin Polymers: Innovative Materials for High-Density Multiwell Plates

Abstract: Extension of ultra-high-throughput experiment (UHTE) approaches to new assay methodologies is often limited by compromised data quality when samples are miniaturized. Overcoming this challenge requires attending to all components of an automated laboratory system contributing to assay variability. A key but often neglected source is the high-density multiwell platform or microtiter plate. Materials from which plates are fabricated may degrade or otherwise compromise an assay through a variety of sources, inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 26 publications
1
45
0
Order By: Relevance
“…[ 17 ] Subsequently, using this casting as a mold, geometrical analogs were made in cyclic olefi n copolymer (COC), an amorphous transparent copolymer that is gaining attention for its optical clarity, biocompatibility, and structural strength. [ 18,19 ] A schematic of the entire process is shown in Figure 1 A. Scanning electron microscopy (SEM) images of an original MN crystal and its analog in COC (Figure 1 B1,C1, respectively) demonstrated that it was possible to reproduce the needle-like shape of the crystal in its original size. High-magnifi cation SEM images (insets in Figure 1 B1,C1) demonstrated Functional biomaterials are gaining importance in regenerative medicine as alternatives to classical treatments based on patient's own tissue, the limited supply of which is an important concern.…”
Section: Doi: 101002/adma201504589mentioning
confidence: 99%
“…[ 17 ] Subsequently, using this casting as a mold, geometrical analogs were made in cyclic olefi n copolymer (COC), an amorphous transparent copolymer that is gaining attention for its optical clarity, biocompatibility, and structural strength. [ 18,19 ] A schematic of the entire process is shown in Figure 1 A. Scanning electron microscopy (SEM) images of an original MN crystal and its analog in COC (Figure 1 B1,C1, respectively) demonstrated that it was possible to reproduce the needle-like shape of the crystal in its original size. High-magnifi cation SEM images (insets in Figure 1 B1,C1) demonstrated Functional biomaterials are gaining importance in regenerative medicine as alternatives to classical treatments based on patient's own tissue, the limited supply of which is an important concern.…”
Section: Doi: 101002/adma201504589mentioning
confidence: 99%
“…Among them, the unique properties of COP, including high resistance to chemicals, high biological compatibility, high transparency in the visible and near-ultraviolet regions of the spectrum, low autofluorescence, low water absorption, low oxygen and moisture permeability, and low gas emissions, make it a strong candidate material for IVD formats [26][27][28].…”
Section: Cyclic Olefin Copolymermentioning
confidence: 99%
“…In addition, they are widely used in the field of diagnostics for microwell plates as well as microfluidic devices and biodiagnostic chips [11][12][13][14][15][16][17][18][19][20][21][22]. COC have a low density and low autofluorescence [12,23].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, they have attracted considerable recent attention as substrate for biochips [24,25]. COC are also used for biosensor technology [26,27], DNA immobilization [28], microarrays, nucleic acid purification and immunoassays [17,[29][30][31][32][33]. The use of a blend of COC with polyethylene for the creation of bone replacement materials has also been reported [34].…”
Section: Introductionmentioning
confidence: 99%